2020
DOI: 10.5937/ijcrsee2002001g
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Metacognitive Aspects of the Development of Lifelong Learning Competencies in Law Students

Abstract: Lifelong learning is one of the main trends in educational and social policy in Europe, aimed at ensuring professional realization and social integrity of an individual. The article describes cognitive and metacognitive aspects of the formation of learning competence, as well as predisposition of law students to lifelong learning. A survey of 218 students and masters was conducted, data on the most popular and effective forms of knowledge acquisition (experience of formal, nonformal and informal learning over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Piaget's learning theory provides an explanation that students (S-F1 subjects) are involved in reconstructive generalization because they try to assimilate experiences with their schemes (Dorko, 2019), adapt new knowledge (S-M1 subjects) in case of disturbances and imbalances, and modify and rearrange schemes (subject S-R1) to balance back so that the development of cognitive structures occurs (Bormanaki & Khoshhal, 2017;Dorko, 2019;Grokholskyi et al, 2020). In the context of mathematics learning, it has been shown that the construction of cognitive structures (knowledge) in the construction of cognitive structures (knowledge) has a strong relationship between the process of assimilation and accommodation and the process of equilibrium (equilibration) in the development of students' cognitive structures.…”
Section: Discussionmentioning
confidence: 99%
“…Piaget's learning theory provides an explanation that students (S-F1 subjects) are involved in reconstructive generalization because they try to assimilate experiences with their schemes (Dorko, 2019), adapt new knowledge (S-M1 subjects) in case of disturbances and imbalances, and modify and rearrange schemes (subject S-R1) to balance back so that the development of cognitive structures occurs (Bormanaki & Khoshhal, 2017;Dorko, 2019;Grokholskyi et al, 2020). In the context of mathematics learning, it has been shown that the construction of cognitive structures (knowledge) in the construction of cognitive structures (knowledge) has a strong relationship between the process of assimilation and accommodation and the process of equilibrium (equilibration) in the development of students' cognitive structures.…”
Section: Discussionmentioning
confidence: 99%
“…Lifelong learning is characterized by being a conscious, person-centered action, the social and collaborative nature of which is particularly important (Grokholskyi et al, 2020). In this regard, the PLE approach may be complementary in successfully achieving the skills and carrying out the main activities of LLL, which are extremely important for formal and informal educational processes (Sentürk & Duran, 2020).…”
Section: Study Objectivesmentioning
confidence: 99%
“…The acquisition and reinforcement of LLL skills brings many benefits (Grokholskyi et al, 2020) which can be grouped in two aspects: on the one hand, it reduces students' gaps in training, and on the other, it helps to deal with workplace related challenges (Caspersen & Smeby 2020). As a response to the new social demands and challenges, some higher education institutions, not exempt from the pressure of globalization, are making changes in how they manage education (Neelam et al, 2020), leading to new study plans, innovative methodologies, research projects, and extension processes.…”
Section: Introductionmentioning
confidence: 99%
“…Students detail their cognitive needs, raise their general cognitive activity and increase their selectivity in information acquisition strategies while at university. The process of building learning capacities begins with the experience of diverse learning activities and the resulting changes in the cognitive domain (Grokholskyi et al, 2020). Cognitive learning accomplishments are a specific level of academic aptitude gained through standardised exam results (Tuaputty et al, 2021).…”
Section: Conceptual or Theoretical Frameworkmentioning
confidence: 99%